Neodymium-iron-boron rare earth magnet and preparation method thereof

By designing NdFeB rare earth magnets without heavy rare earths, using the combination of the main phase and multiple grain boundary phases, the problem of high cost of NdFeB rare earth magnets in the prior art is solved, and high-performance and low-cost magnet preparation is achieved.

CN119601333APending Publication Date: 2025-03-11YANTAI DONGXING MAGNETIC MATERIALS INC

Patent Information

Application Number
CN202411796287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing neodymium iron boron rare earth magnets are costly, mainly due to the high cost of heavy rare earths and the difficulty in maintaining high performance without using heavy rare earths.

Method used

A neodymium iron boron rare earth magnet containing no heavy rare earths is designed, which includes the main phase, the two-particle grain boundary phase and the triangular grain boundary phase. The main phase is R2T14B phase, the two grain boundary phases contain copper-rich phases and needle-shaped ZrBx or TiBx phases, and the triangular grain boundary phases contain FCC-type NdOx phase, RCu phase, RGa phase and needle-shaped ZrBx or TiBx phases.

Benefits of technology

The high performance of neodymium iron boron rare earth magnets without heavy rare earths is achieved. The magnet uniformity and squareness are good, and the coercive force and residual magnetism can be controlled by the design of the grain boundary phase, and have good high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601333A_ABST
    Figure CN119601333A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of neodymium-iron-boron magnets, in particular to a neodymium-iron-boron rare earth magnet and a preparation method thereof.The neodymium-iron-boron rare earth magnet is a sintered neodymium-iron-boron permanent magnet and comprises a main phase, a two-particle grain boundary phase and a triangular area grain boundary phase; the main phase comprises an R2T14B phase, R refers to at least one of Nd and Pr, T refers to Fe, and Co at least contains Fe; the two-particle grain boundary phase comprises a grain boundary copper-rich phase, and / or a needle-shaped ZrBx phase with the width of 10-50 nm, and / or a needle-shaped TiBx phase with the width of 10-50 nm; the triangular region grain boundary phase comprises an FCC type NdOx phase, an RCu phase, an RGa phase, an R-rich phase, a 6: 14 phase and / or a needle-shaped ZrBx phase with the width of 10-50 nm and / or a needle-shaped TiBx phase with the width of 10-50 nm, the neodymium-iron-boron rare earth magnet does not contain heavy rare earth and is good in uniformity, and the coercive force and residual magnetism can be regulated and controlled through the design of the grain boundary phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of neodymium iron boron magnets, and in particular to a neodymium iron boron rare earth magnet and a preparation method thereof. Background Art

[0002] In recent years, NdFeB rare earth magnets have developed rapidly and are widely used in high-tech fields such as new energy vehicles, air conditioning compressors, and robots. Due to its high cost, reducing costs is an important issue. Therefore, NdFeB rare earth magnets that do not contain heavy rare earths and have high performance have become the first demand of current customers.

[0003] Heavy rare earth grain boundary diffusion is the most effective method to improve the performance of NdFeB rare earth magnets, but heavy rare earths are of low abundance and expensive, and the cost of heavy rare earth grain boundary diffusion is still very high. With the sharp increase in demand for high-performance NdFeB rare earth magnets and the soaring price of heavy rare earths, not using heavy rare earths to reduce costs has become a key issue. The main part of the cost of NdFeB rare earth magnets is the proportion of heavy rare earths, so researchers, especially those in enterprises, focus on the research direction of manufacturing NdFeB rare earth magnets with low or no heavy rare earths. Therefore, designing NdFeB rare earth magnets that do not contain heavy rare earths and have high performance has become a hot research issue.

[0004] The Chinese invention patent with the authorization announcement number CN110299237B discloses RTB sintered magnets containing R2T 14 B's crystals are composed of multiple main phase particles, and multiple grain boundary multiple points which are grain boundary phases surrounded by at least three of the main phase particles, the multiple grain boundary multiple points are classified into at least two phases of a transition metal-rich phase and an R-rich phase, the R-rich phase is classified into at least two phases of a Cu-poor phase and a Cu-rich phase. This type of magnet has excellent performance in the absence of heavy rare earth content or with trace amounts of heavy rare earth.

[0005] The Chinese invention patent with the authorization announcement number CN111724959B discloses an RTB permanent magnet, wherein the RTB permanent magnet contains Ga, R is one or more rare earth elements, T is Fe or Fe and Co, B is boron, and contains a material having R2T 14 A main phase grain composed of crystal grains of a B-type crystal structure and a grain boundary formed by two or more adjacent main phase grains, the grain boundary comprising R6T 13 Ga phase, this type of magnet has excellent performance without rare earth content. The present application proposes a high-performance heavy rare earth-free magnet with a new structure and a preparation method thereof, which are different from the above two disclosed solutions. Summary of the invention

[0006] Technical purpose: In order to overcome the deficiencies in the prior art, the present invention provides a neodymium iron boron rare earth magnet.

[0007] Technical solution: To achieve the above purpose, the present invention discloses a NdFeB rare earth magnet, which is a sintered NdFeB permanent magnet, comprising a main phase, a two-grain grain boundary phase and a triangular region grain boundary phase;

[0008] The main phase contains R2T 14 B phase, the unit is atomic percentage, R refers to at least one of Nd and Pr, T refers to at least Fe among Fe and Co;

[0009] The two-grain grain boundary phase comprises:

[0010] The content of the copper-rich phase at the grain boundary satisfies 1.5<Cu / R≤2 within 20nm near the main phase interface, and 1<Cu / R≤1.5 within 50nm at the center of the grain boundary.

[0011] and / or needle-shaped ZrBx phase, with a width of 10 to 50 nm,

[0012] and / or needle-shaped TiBx phase, with a width of 10 to 50 nm;

[0013] The triangular region grain boundary phase includes: FCC-type NdOx phase, RCu phase, where 1<Cu / R≤1.5, RGa phase, where 0.1<Ga / R≤0.5, R-rich phase, 6:14 phase, and / or needle-shaped ZrBx phase with a width of 10 to 50 nm, and / or needle-shaped TiBx phase with a width of 10 to 50 nm.

[0014] Furthermore, based on the unit mass percentage of 100%, it includes the following components: R: 29.5-33.5%; B: 0.85-1.05%; Al: 0.05-0.8%; Cu: 0.4-2.0%; Ga: 0.3-0.6%; Co: 0.5-2.0%; Zr or Ti: 0.15-0.5%, and the rest are Fe and unavoidable impurities.

[0015] Furthermore, the R may also contain at least one of La, Ce, Sm, Y, Gd, Dy, Tb, and Ho.

[0016] The present application also provides a method for preparing the above-mentioned NdFeB rare earth magnet, comprising the following steps:

[0017] S1: subjecting the raw material to hydrogen absorption and dehydrogenation treatment to obtain a thin strip of the main phase alloy and a thin strip of the related phase after hydrogen treatment, respectively;

[0018] S2: Mix the main phase alloy ribbon obtained in step S1 with the related phase ribbon in a certain proportion, and mechanically crush them to allow the amorphous alloy and the main alloy to form a solid solution, crush the mixed powder into powder, and perform magnetic field molding to obtain a blank;

[0019] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0020] Furthermore, in step S1, the hydrogen absorption temperature is 50-100° C., the dehydrogenation temperature is 500-650° C., and the dehydrogenation time is 3-7 hours.

[0021] Furthermore, in step S2, the mechanical crushing particle size is 10-25 μm, the powder particle size D50 obtained by crushing and pulverizing is 2-7 μm, and the billet density is 4.0-4.5 g / cm 3 .

[0022] Furthermore, in step S3, the sintering temperature is 950-1100° C., and the insulation time is 4-15 hours; the first-stage aging temperature is 700-900° C., and the insulation time is 3-7 hours; the second-stage aging temperature is 430-550° C., and the insulation time is 3-7 hours.

[0023] The beneficial effects of the present invention are:

[0024] 1. The NdFeB rare earth magnet in this method does not contain heavy rare earth, and the magnet has good uniformity and squareness, both of which are above 0.97.

[0025] 2. The coercive force and remanence of NdFeB rare earth magnets can be controlled by the design of grain boundary phase.

[0026] 3. The grain boundary phase contains a thicker non-magnetic phase, which plays a good role in magnetic isolation and increases the coercive force of the magnet.

[0027] 4. The grain boundary phase contains uniform needle-shaped ZrBx phase or TiBx phase, which has good high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a cross-sectional schematic diagram of the NdFeB rare earth magnet of the present invention;

[0029] Figure 2 Schematic diagram of the microstructure of the NdFeB rare earth magnet of the present invention; wherein, the number 1 is the main phase particle (one); the number 2 is the main phase particle (two); the number 3 is the triangular region grain boundary phase (three); the number 4 is the two-particle grain boundary phase; the number 5 is the needle-shaped ZrBx phase and the needle-shaped TiBx phase;

[0030] Figure 3 The scanning electron microscope image of the NdFeB rare earth magnet of the present invention; wherein, the label 1 is the main phase; the label 2 is the HCP type Nd-rich phase; the label 3 is the RCu phase; the label 4 is the RGa phase; the label 5 is the R-rich phase; the label 6 is the 6:14 phase; the label 7 is the needle-shaped ZrBx phase and the needle-shaped TiBx phase;

[0031] Figure 4 The FCC structural diffraction pattern of the phase structure NdOx of Example 1 of the present invention;

[0032] Figure 5 The phase structure 6:14 diffraction pattern of Example 1 of the present invention;

[0033] Figure 6 The diffraction pattern of the phase structure R-rich phase structure of Example 1 of the present invention;

[0034] Figure 7 Schematic diagram of the phase diagram and position of the grain boundaries of two particles in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The following is combined with Figure 1 —Attachment Figure 7 The principles and features of the present invention are described, and the examples given are only used to explain the present invention, not to limit the scope of the present invention.

[0036] A NdFeB rare earth magnet is a sintered NdFeB permanent magnet, comprising a main phase, a two-grain grain boundary phase and a triangular region grain boundary phase;

[0037] The main phase contains R2T 14 B phase, R refers to a rare earth element, which contains at least one of Nd and Pr, and T refers to Fe or Fe and Co, and the unit is atomic percentage; R2T 14 The B phase is a single main phase particle, and the average particle size of the main phase particles ranges from 2 μm to 7 μm. In addition, R may contain at least one of La, Ce, Sm, Y, Gd, Dy, Tb, and Ho in addition to at least one of Nd and Pr.

[0038] The two-grain boundary phase contains:

[0039] The content of the copper-rich phase at the grain boundary satisfies 1.5<Cu / R≤2 within 20nm near the main phase interface, and 1<Cu / R≤1.5 within 50nm at the center of the grain boundary.

[0040] and / or needle-shaped ZrBx phase, with a width of 10 to 50 nm,

[0041] and / or needle-shaped TiBx phase, with a width of 10 to 50 nm;

[0042] The grain boundary phases in the triangular region include: FCC-type NdOx phase, RCu phase, where 1<Cu / R≤1.5, RGa phase, where 0.1<Ga / R≤0.5, R-rich phase, 6:14 phase, and / or needle-shaped ZrBx phase with a width of 10 to 50 nm, and / or needle-shaped TiBx phase with a width of 10 to 50 nm.

[0043] Specifically, the needle-shaped ZrBx phase or TiBx phase refers to a ZrB phase or a ZrB2 phase.

[0044] The main phase, the two-grain boundary phase and the triangular region grain boundary phase exist in the cross section perpendicular to the C axis or parallel to the C axis, and the phase in the triangular region grain boundary phase may exist in the two-grain boundary phase.

[0045] Specifically, Figure 1 As shown, any part of the interface is observed for sample preparation and testing. The testing method is to use scanning electron microscopy (SEM) for microstructural observation and transmission electron microscopy (TEM) for grain boundary microstructure, microelement distribution, etc. The screenshot is a rectangle, but its actual shape is not limited to a rectangle, it can also be a square, tile-shaped, steamed bun-shaped, cylindrical, bow-shaped, etc.

[0046] like Figure 2 As shown, the NdFeB rare earth magnet has main phase particles (I) and main phase particles (II). The main phase particles (I) and the main phase particles (II) have the same composition, or they may have different compositions, such as double main phases, three main phases, etc. The main phase may further contain Tb2Fe 14 B. Dy2Fe 14 B. Ho2Fe 14 B. Gd2Fe 14 B. Y2Fe 14 B. La2Fe 14 B. Ce2Fe 14 B, etc. In addition to the above elements, the main phase particles may also contain Al, Ga, Cu and other elements. At the same time, the main phase particles (I) and the main phase particles (II) may have a certain concentration gradient, such as a concentration gradient of heavy rare earths Tb, Dy, Ho, Cu, Al, Ga, etc. Figure 3 Note 1 in .

[0047] Figure 2The triangular grain boundary phase (III) is a phase other than the main phase and the two-grain grain boundary phase. The triangular grain boundary phase (III) contains the FCC phase of NdOx, and the triangular grain boundary phase contains a certain proportion of neodymium oxide of the FCC phase. The mismatch between the main phase and FCC-NdOx in

[011] and (111) is only 4.2%, which increases the magnetic isolation ratio of the grain boundary of the NdFeB rare earth magnet, thereby increasing the coercive force of the magnet. The oxygen content of this phase is generally 10at% to 45at%. At the same time, since the NdFe triangular grain boundary phase can further contain DHCP-type Nd-rich phase and HCP-type Nd-rich phase. The DHCP-type Nd-rich phase is more present in the two-grain grain boundary phase or the triangular grain boundary phase, and the HCP-type Nd-rich phase is more due to improper oxygen content control or excessive storage time. The HCP-type Nd-rich phase is formed due to the increase in oxygen content. The content of HCP type Nd-rich phase is very small, accounting for less than 15% of the grain boundary phase in the triangle area. Figure 3 Note 2 in .

[0048] The triangular grain boundary phase (three) contains RCu phase, which can be PrCu phase, NdCu phase, or NdPrCu, etc. The atomic ratio of RCu phase satisfies 1<Cu / R≤1.5, where R refers to the sum of the number of atoms of Nd and Pr elements. At the same time, since the triangular grain boundary phase of NdFe can further include LaCu, CeCu, GdCu, DyCu, TbCu, HoCu and other phases, and their atomic ratios satisfy 1<Cu / R≤1.5, the RCu phase accounts for between 15% and 50% of the triangular grain boundary phase. RCu corresponds to Figure 3 Note 3 in .

[0049] Figure 2 The grain boundary phase (three) in the middle triangle zone contains RGa phase, which can be PrGa phase, NdGa phase, or NdPrGa, etc. The atomic ratio of the RGa phase satisfies 0.1<Ga / R≤0.5, where R refers to the sum of the number of atoms of Nd and Pr elements. At the same time, the grain boundary phase in the triangle zone can further include LaGa, CeGa, GdGa, DyGa, TbGa, HoGa and other phases, and their atomic ratios satisfy 0.1<Ga / R≤0.5. At the same time, the RGa phase can further contain composite phases such as Co, Al, Cu, Fe, Mg, Zn, Mo, Ti, Zr, Sb, and Bi. The RGa phase occupies 10% or less of the triangle zone, and the corresponding RGa phase is 0.1<Ga / R≤0.5. Figure 3 Note 4 in the figure.

[0050] Figure 2The middle triangular grain boundary phase (three) contains an R-rich phase, and the R-rich phase is mainly composed of R, where R refers to the sum of the atomic numbers of Nd and Pr elements. Furthermore, the R elements of the triangular grain boundary phase may also include rare earth elements such as La, Ce, Sm, Y, Gd, Dy, Tb, and Ho. At the same time, R may contain a certain amount of Fe, with a content range of 0 to 20at%. Further, R may also contain elements such as Co, Al, Cu, Fe, Mg, Zn, Mo, Ti, Zr, Sb, and Bi, but the content of these elements is not fixed, and sometimes the content is zero. The R-rich phase may sometimes exist in an amorphous form, and R-rich accounts for 35% or less of the triangular grain boundary phase. R-rich corresponds to Figure 3 Note 5 in the figure.

[0051] Figure 2 The grain boundary phase (III) in the middle triangle region contains a 6:14 phase, which satisfies the ratio of the 6:14 phase. It is mainly R6T 13 (GaCu)1 phase exists. The 6:14 phase can also contain at least one of Al, Mg, Zn, Ti, Zr, Mo, Sb, and Bi. In addition, the T element refers to at least one of Fe and Co. R mainly refers to Pr and Nd. In addition, it can also contain rare earth elements such as La, Ce, Sm, Y, Gd, Dy, Tb, and Ho. There are at least 4 elements in the 6:14 phase. The 6:14 phase accounts for 20% to 50% of the grain boundary phase in the triangular region. 6:14 corresponds to Figure 3 Note 6 in the figure.

[0052] Figure 2 The grain boundary phase (three) in the middle triangular region contains a needle-shaped ZrBx phase with a width of 10-50nm, and / or a needle-shaped TiBx phase with a width of 10-50nm. The needle-shaped ZrBx phase and the needle-shaped TiBx phase are mainly high melting point phases, mainly referring to ZrB2 or TiB2 phases, and the high melting point phases may also contain high melting point phases such as Mo and W. Furthermore, the shapes of the high melting point phases are sometimes point-shaped, line-shaped, etc. Due to the presence of the high melting point phase, the magnetic domain is pinned, so that the magnet has a large coercive force and high temperature resistance. The needle-shaped ZrBx phase and the needle-shaped TiBx phase are mainly distributed in the triangular region grain boundary phase or the two-grain grain boundary phase, and the distribution position is along the grain boundary or at the edge or center of the triangular region. The high melting point phase can be distributed in the R-rich phase, the 6:14 phase, the RCu phase, the RGa phase, or in close proximity to the neodymium oxide. The distribution of needle-shaped ZrBx phase and needle-shaped TiBx phase is dispersed and not fixed in a specific phase. The distribution positions of needle-shaped ZrBx phase and needle-shaped TiBx phase are shown in Figure 2 The mark 5 (in the form of a black needle) corresponds to Figure 3 Note 7 in the figure.

[0053] The triangular grain boundary phase (three) includes the FCC phase of NdOx, RCu phase, RGa phase, 6:14 phase, or needle-shaped ZrBx phase or TiBx phase. These phases do not necessarily exist alone, but may exist in a triangular region in an intersecting manner. Two phases exist in an intersecting manner, such as the RCu phase and the FCC phase of NdOx, the RGa phase and the FCC phase of NdOx, the Nd-rich phase and the FCC phase of NdOx, the Nd-rich phase and the 6:14 phase, the 6:14 phase and the needle-shaped ZrBx phase, and the 6:14 phase and the needle-shaped TiBx phase; three phases exist in an intersecting manner, such as the Nd-rich phase and the 6:14 phase and the needle-shaped ZrBx phase or the needle-shaped TiBx phase, or they may exist in a triangular region alone, such as the FCC phase of NdOx or the 6:14 phase. By using transmission electron microscopy to test, Figure 4 The FCC structure diffraction pattern of NdOx, which is the phase structure of Example 1, verifies the existence of the FCC phase of NdOx. Figure 5 It means that the phase structure 6:14 phase structure diffraction pattern of Example 1 verifies the existence of the 6:14 phase. Figure 6 It means that the diffraction pattern of the phase structure R-rich phase structure of Example 1 verifies the existence of the R-rich phase.

[0054] Figure 7Refers to the two-grain grain boundary diagram and position schematic diagram of Example 1 (photographed by transmission electron microscope). As shown in the position a in the figure, the copper-rich phase of the grain boundary is within 20nm near the main phase interface, satisfying 1.5<Cu / R≤2, and a is equal to 20nm. As shown in the position b in the figure, the copper-rich phase of the grain boundary is 50nm from the center line of the grain boundary, satisfying 1<Cu / R≤1.5, and b is equal to 50nm. The two-grain grain boundary refers to the grain boundary between two main phase particles. The width of the grain boundary varies from 2nm to 500nm, and the average width is generally 100nm. The composition distribution of the grain boundary has obvious regularity, that is, the Cu content in the edge part is significantly increased, and the Cu content is higher than other positions of the grain boundary. The position where the Cu content increases, the content of Pr and Nd is significantly reduced, generally within 20nm near the main phase interface. At the same time, it is not ruled out that there are similar rules farther away from the main phase interface, such as 30nm near the interface. The content of Cu, Nd, and Pr is significantly higher than the content of other elements in the grain boundary. Further other R elements may have similar rules. R mainly refers to Pr and Nd. In addition, it can also contain rare earth elements such as La, Ce, Sm, Y, Gd, Dy, Tb, and Ho. Furthermore, elements such as Al, Cu, Mg, and Zn can also have similar rules to Cu, that is, the content of these elements in the edge part is significantly increased, higher than other positions at the grain boundary. The content of elements such as Pr and Nd at these positions is significantly reduced, generally within the range of a value near the main phase interface. At the same time, it is not ruled out that there are similar rules farther away from the main phase interface, such as positions within the range of interface a. The copper-rich phase at the grain boundary is within the center line b of the grain boundary, satisfying 1<Cu / R≤1.5. Similarly, this position may have a longer center line length. The content of Cu and rare earth Pr and Nd is significantly higher than the distribution of other elements. The Cu content is higher than the R content, satisfying 1<Cu / R≤1.5. R mainly refers to Pr and Nd. In addition, it can also contain rare earth elements such as La, Ce, Sm, Y, Gd, Dy, Tb, and Ho. Furthermore, elements such as Al, Cu, Mg, and Zn may also have similar rules to Cu.

[0055] Needle-shaped ZrBx phase, width 10-50nm, needle-shaped TiBx phase, width 10~50nm, R refers to at least one of Nd and Pr, and the unit is atomic percentage. This phase distributed in the two-grain grain boundary phase can be a high melting point phase distributed along the grain boundary, or it can be a needle-shaped object distributed perpendicular to the grain boundary. Zr and Ti are high melting point elements, so the high melting point phase will also contain high melting point phases such as Mo and W. Furthermore, the shape of the high melting point phase is in the shape of dots, lines, etc. Due to the existence of this high melting point phase, it plays a role in pinning the magnetic domains, and the coercive force of the magnet has a larger coercive force and high temperature resistance. This phase corresponds to Figure 3 Mark 7 in the figure shows the location of the two-grain grain boundary phase.

[0056] NdFeB rare earth magnets have high performance, including high coercivity, remanence and squareness.

[0057] Therefore, the magnet satisfies any one of the following:

[0058] The two-grain grain boundary phase is within 20nm near the main phase interface and satisfies 1.5<Cu / (Nd+Pr)≤1.6, 1.5<Cu / (Nd+Pr)≤1.7, 1.5<Cu / (Nd+Pr)≤1.8, 1.5<Cu / (Nd+Pr)≤1.9, 1.5<Cu / (Nd+Pr)≤2.0, 1.6≤Cu / (Nd+Pr)≤1.7, 1.6≤Cu / (Nd+Pr)≤1.8, 1.6≤Cu / (Nd+Pr)≤1.9, 1.6≤Cu / (Nd+Pr)≤2.0, 1.7≤Cu / (Nd+Pr)≤1.8, 1.7≤Cu / (Nd+Pr)≤1.9, 1.7≤Cu / (Nd+Pr)≤2.0,

[0059] At the center of the two-grain grain boundary phase, the copper-rich phase at the grain boundary is within 100nm from the center of the grain boundary, and the RCu phase in the triangular area satisfies 1<Cu / R≤1.2, 1<Cu / R≤1.3, 1<Cu / R≤1.4, 1<Cu / R≤1.5, 1.1<Cu / R≤1.2, 1.1<Cu / R≤1.3, 1.1<Cu / R≤1.4, 1.1<Cu / R≤1.5, 1.2<Cu / R≤1.3, 1.2<Cu / R≤1.4, 1.2<Cu / R≤1.5, 1.3<Cu / R≤1.4, 1.3<Cu / R≤1.5, 1.4<Cu / R≤1.5.

[0060] RGa phase in the triangular region, RGa phase satisfies 0.1<Ga / R≤0.2, 0.1<Ga / R≤0.3, 0.1<Ga / R≤0.4, 0.1<Ga / R≤0.5, 0.2<Ga / R≤0.3, 0.2<Ga / R≤0.4, 0.2<Ga / R≤0.5, 0.3<Ga / R≤0.4, 0.3<Ga / R≤0.5, 0.4<Ga / R≤0.5.

[0061] The remanence of NdFeB rare earth magnets is mainly affected by factors such as the volume fraction of the positive domain, the proportion of non-magnetic phase, relative density, and the orientation of the magnetic domain. Therefore, these parameters can be compared in the process of designing magnets with different remanence. The factors affecting the coercive force of NdFeB magnets are the anisotropy field, structure factor, demagnetization factor, and saturation magnetic polarization intensity of the magnet. The squareness is mainly affected by the uniformity of the magnet. Therefore, the mechanism of high performance of NdFeB rare earth magnets is analyzed as follows:

[0062] The grain boundary phase in the triangular region includes FCC phase, RCu phase, RGa phase, 6:14 phase, or needle-shaped ZrBx phase, or TiBx phase of NdOx; Cu-rich phase, Nd-rich phase, 6:14 phase, etc. in the two-grain grain boundary phase.

[0063] The triangular grain boundary phase contains the FCC phase of NdOx, which has a low mismatch with the main phase, and can optimize the microstructure of the NdFeB rare earth magnet. After the mismatch is reduced, the stray field formed is reduced, and the defect ratio is reduced, thereby improving the coercivity of the magnet. The triangular grain boundary phase contains the RCu phase and the RGa phase. These two phases are non-magnetic phases, which can magnetically isolate more than two adjacent main phase grains, thereby improving the coercivity of the magnet. The triangular grain boundary phase contains the weak magnetic phase 6:14 phase and the Cu-rich phase of the two-grain grain boundary phase, which can form a grain boundary phase with good continuity. At the same time, the grain boundary phase of a certain thickness formed can effectively isolate the main phase particles, thereby increasing the coercivity of the magnet. The needle-shaped ZrBx phase or needle-shaped TiBx phase in the triangular grain boundary phase and the two-grain grain boundary phase can prevent the magnetic deflection of the grain magnetic domain and play a pinning role, thereby improving the coercivity of the magnet. The ratio of the triangular grain boundary phase, the two-grain grain boundary phase and the main phase is a factor that determines the size of the residual magnetism. In addition, under the same magnetization intensity, the triangular grain boundary phase containing NdOx's FCC phase, RCu phase, RGa phase, 6:14 phase, or needle-shaped ZrBx phase or TiBx phase and the Cu-rich phase in the two-grain grain boundary phase can better increase the volume fraction of the forward domain of the magnet, thereby increasing the remanence of the magnet. In addition, without generating bright spots in the magnet, increasing the sintering temperature can increase the relative density of the magnet, thereby increasing the remanence of the magnet, which is in line with the principle of increasing the remanence of the magnet.

[0064] The mechanism by which the NdFeB rare earth magnet increases the coercive force of the magnet is not limited to the above-mentioned mechanism.

[0065] The R content of NdFeB rare earth magnets is 29.5-33.5%, and the optimal range is 30-32%, and the ratio is mass percentage. Rare earth element R mainly refers to at least one of Pr and Nd elements. If the magnet has excellent performance, a special microstructure needs to be designed, such as the structural features in this scheme. R mainly participates in the construction of the main phase and the grain boundary phase. R participates in the construction of the main phase, that is, the formation of R2T 14 B, such as Nd2Fe 14 B, Pr2Fe 14B, etc.; in addition, R participates in the construction of grain boundary phases, including the construction of triangular zone grain boundary phases and two-particle grain boundary phases. The grain boundaries of the magnet are constructed into a magnet with a continuous structure and a grain boundary phase of corresponding composition. The higher the proportion of R elements, the better the magnetic isolation effect of the microstructure, thereby greatly increasing the coercive force of the magnet. The grain boundaries are designed according to the excess proportion of R participating in the construction of the main phase. The higher the proportion of the grain boundary, the lower the remanence of the magnet. Depending on the required microstructure, magnets with different compositions are designed to obtain NdFeB rare earth magnets with different performances.

[0066] The B content of NdFeB rare earth magnets is 0.85-1.05%, and the optimal range is 0.85-0.95%, the ratio is mass percentage. 14 The tetragonal phase of B is crucial, in which B plays a role in expanding the atomic distance between Fe-Fe and reducing the number of Fe's nearest neighbor atoms. Therefore, the addition of B greatly improves the magnetic properties of the magnet. When the B content increases from 0, the α-Fe, Nd2Fe 17 phase gradually disappears, Nd2Fe 14 The B tetragonal phase is gradually formed. Therefore, by controlling the B content in the magnet, the proportion of the main phase, the proportion and composition of the grain boundary phase can be controlled, thereby controlling the remanence and coercive force of the magnet. In addition, the composition of the grain boundary phase of the magnet can be further designed by adding other elements. Adding a certain Cu content can make the triangular grain boundary phase or the two-grain grain boundary phase of the magnet contain a Cu-rich phase. Since Cu is a non-magnetic element, a certain Cu content can increase the coercive force of the magnet. The grain boundary phase contains ZrB phase or TiB phase, and the phase ratio is 1:1 phase or 1:2 phase. There may be other B-containing alloy phases.

[0067] The Al content of NdFeB rare earth magnets is 0.05-0.8%, and the optimal range is 0.1%-0.6%, the ratio is mass percentage. The addition of Al element can refine the grain of the main phase, reduce the size of Nd-rich and B-rich phases, and improve the wettability between the Nd-rich phase and the main phase. Al element enters the main phase to participate in the formation of Nd2Fe 14-x BAl x Alternatively, a 6:14 phase containing Al is formed in the grain boundary phase. The 6:14 phase containing Al can exist in the triangular region or in the two-grain grain boundary phase. Al elements can exist in various phases as interstitial atoms, including 6:14 phase, copper-rich phase, Nd-rich phase, etc.

[0068] The Cu content of NdFeB rare earth magnets is 0.4-2.0%, which can range from 1.5-2.0%, 0.4-1.0%, or 1.0-1.5%, and the ratio is mass percentage. The Cu element can improve the irreversible loss of the magnet, can be evenly distributed in the Nd-rich phase, improve the grain boundary phase, and resist corrosion and oxidation. The Cu element can replace the Fe atoms near the grain boundary of the main phase to form Nd2Fe 14-x BCU x phase or forms a Cu-containing 6:14 phase in the grain boundary phase. The Cu element can form a copper-rich phase, which can exist in the triangular grain boundary phase or the two-grain grain boundary phase. In short, the Cu element can exist in various phases as an interstitial atom, including the 6:14 phase, the copper-rich phase, the Nd-rich phase, etc.

[0069] The Ga content of NdFeB rare earth magnets is 0.3-0.6%, which is a mass percentage. The Ga element can lower the melting point of the grain boundary, evenly distribute in the grain boundary phase, improve the structure of the grain boundary phase, and repair the defects of the magnet. The Ga element can replace the Fe atoms near the grain boundary of the main phase to form Nd2Fe 14-x BG x Phase or form Ga-containing 6:14 phase in the grain boundary phase. Ga element can form Ga-rich phase. This phase can exist in the triangular grain boundary phase or the two-grain grain boundary phase. In short, Ga element can exist in various phases as an interstitial atom, including 6:14 phase, copper-rich phase, Nd-rich phase, etc.

[0070] The Co content of NdFeB rare earth magnets is 0.5-2.0%, and the ratio is mass percentage. The Co element mainly improves the high temperature stability of the magnet, forms stable Nd3Co at the grain boundary, and can also improve the corrosion resistance of the magnet. The Co element can also be 0.5-1.0%. Similarly, the Co element can exist in various phases as an interstitial atom, including 6:14 phase, copper-rich phase, Nd-rich phase, main phase, etc.

[0071] The Zr or Ti content of NdFeB rare earth magnets is 0.15-0.5%, and the ratio is mass percentage. As high melting point elements, Zr or Ti elements can refine the grains and form high melting point B or C compounds. Similarly, Zr or Ti elements can exist in various phases as interstitial atoms, including 6:14 phase, copper-rich phase, Nd-rich phase, etc.

[0072] The impurity C content of NdFeB rare earth magnets is below 1200ppm, and the optimal content is between 300 and 800ppm. Too high C content will damage the main phase, resulting in poor continuity of the grain boundary phase and low performance.

[0073] The impurity O content of NdFeB rare earth magnets is below 900ppm, and the optimal content is between 200 and 700ppm. If the O content is too high, a large amount of HCP-type Nd oxides will be formed. The HCP-type lattice damage thickness is large and has many defects, which leads to an increase in the mismatch between this phase and the main phase, and more stray fields, which leads to a sharp decline in magnet performance.

[0074] The impurity N content of NdFeB rare earth magnets is below 1500ppm, and the optimal content is between 500 and 1000ppm. If the N content is too high, rare earth nitrides will be formed, which will lead to a decrease in magnet performance.

[0075] Embodiment 1:

[0076] The method for preparing the above-mentioned NdFeB rare earth magnet comprises the following steps:

[0077] S1: subjecting the raw materials to hydrogen absorption and dehydrogenation treatments to obtain a hydrogen-treated main phase alloy ribbon and a related phase ribbon, respectively. The related phase ribbon may be a copper-rich gallium-rich phase ribbon, etc. The related phase ribbon is a rapidly quenched amorphous ribbon.

[0078] Specifically, the raw materials for preparing the thin strips of the main phase alloy and the thin strips of the related phases of the NdFeB rare earth magnet are determined by composition design. The raw materials used can be metal elements, alloys containing rare earth elements or alloys without rare earth elements, iron, ferroboron, etc. The hydrogen absorption and dehydrogenation treatment can be low-temperature hydrogen absorption treatment or high-temperature hydrogen absorption treatment, and the dehydrogenation treatment can be high-temperature dehydrogenation or low-temperature long-term dehydrogenation.

[0079] Specifically, in this embodiment, a low-temperature hydrogen absorption treatment is adopted, the hydrogen absorption temperature is 50°C, the dehydrogenation temperature is 500°C, the dehydrogenation time is 7 hours, and the thin strip of the relevant phase is the alloy component Pr 60 Nd 10 Cu 20 Ga 10 (atomic ratio) of amorphous quenched strip.

[0080] S2: The main phase alloy ribbon obtained in step S1 is mixed with the related phase ribbon in a certain proportion, and mechanically crushed to allow the amorphous alloy and the main alloy to form a solid solution, thereby introducing the Cu-rich and Ga-rich phases in the grain boundaries; the mixed powder is crushed and pulverized, and the pulverizing process can be ball milling or air flow milling. A small amount of oxygen can be introduced during the pulverizing process to perform magnetic field forming to obtain a blank, and the magnetic field forming is to press-form on one side and magnetic field orientation on the other side at the same time; after magnetic field forming, isostatic pressing can be performed and then sintering and aging can be performed, or sintering and aging can be performed directly.

[0081] Specifically, in this embodiment, the weight ratio of the thin strip of the relevant phase is 2%, the mechanical crushing particle size is 20 μm, the air flow milling is used for powdering, the powder particle size D50 = 3.5 μm, and the density of the blank after magnetic field forming is 4.5 g / cm 3 .

[0082] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0083] The sintering process mainly increases the density and the contact properties between the powder particles, thereby increasing the remanence of the magnet and improving the strength, so that the magnet has the microstructure characteristics of high permanent magnetic properties. This process is mainly liquid phase sintering. During the sintering of the magnet, a high melting point plate, such as a molybdenum plate or a zirconium plate, can be added as a pad. A mixed gas such as nitrogen, argon, and hydrogen can also be introduced to prevent oxidation of the magnet.

[0084] The first stage of aging is to melt the Nd-rich phase, form a flowing liquid phase, and flow and penetrate into the gaps between the powder particles, melt the sharp corners of the grains, melt the sharp corners, and round them to ensure that the grain boundary phase of the magnet is further optimized. In addition, this process can add alloy powder on the surface of the blank, and the alloy powder can be PrNd, PrAl, PrAlCu, PrAlGa, etc.

[0085] In the second stage of aging, the grain boundary phase is transformed into a liquid phase and flows between grains, and is evenly and dispersedly distributed in the grain boundary, making the grain boundary regular and smooth, increasing the difficulty of nucleation of the reverse magnetization domain, and reducing the demagnetization field of the main phase grains. After heat treatment, the distribution of the Nd-rich phase at the grain boundary is sufficient and uniform, which can better isolate the main phase grains, remove the magnetic exchange coupling between the grains, and improve the coercive force of the magnet. After aging, the Hcj (BH) m and squareness are improved. It is mainly to form a Cu or Ga-rich phase and a 6:14 phase, so that the low melting point phase is further evenly and continuously distributed in the grain boundary, so that the Cu or Ga-rich phase and the 6:14 phase can better isolate the main phase, achieve the effect of demagnetization coupling, and further increase the coercive force and squareness of the magnet.

[0086] Specifically, in this embodiment, the sintering temperature is 1070°C, and the temperature is kept for 6 hours; the first-stage aging temperature is 880°C, and the temperature is kept for 3 hours; the second-stage aging temperature is 430°C, and the temperature is kept for 7 hours. The final NdFeB rare earth magnet has the following components per unit mass percentage: PrNd content is 29.5%, Al content is 0.05%, B content is 0.94%, Co content is 0.5%, Cu content is 0.4%, Ga content is 0.3%, Zr content is 0.3%, and the rest is Fe and impurities. The C content in the impurities is 800ppm, the N content is 900ppm, and the O content is 700ppm. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data of the obtained NdFeB rare earth magnet measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument are shown in Table 1; the atomic percentage of each element in the NdFeB rare earth magnet is shown in Table 3.

[0087] Embodiment 2:

[0088] The present embodiment is different from the above-mentioned embodiment 1 in that the above-mentioned method for producing a NdFeB rare earth magnet comprises the following steps:

[0089] S1: subjecting the raw materials to hydrogen absorption and dehydrogenation treatments to obtain a hydrogen-treated main phase alloy ribbon and a related phase ribbon, respectively. The related phase ribbon may be a copper-rich gallium-rich phase ribbon, etc. The related phase ribbon is a rapidly quenched amorphous ribbon.

[0090] Specifically, the raw materials for preparing the thin strips of the main phase alloy and the thin strips of the related phases of the NdFeB rare earth magnet are determined by composition design. The raw materials used can be metal elements, alloys containing rare earth elements or alloys without rare earth elements, iron, ferroboron, etc. The hydrogen absorption and dehydrogenation treatment can be low-temperature hydrogen absorption treatment or high-temperature hydrogen absorption treatment, and the dehydrogenation treatment can be high-temperature dehydrogenation or low-temperature long-term dehydrogenation.

[0091] Specifically, in this embodiment, a room temperature hydrogen absorption treatment is adopted, the dehydrogenation temperature is 600°C, the dehydrogenation time is 5 hours, and the thin strip of the relevant phase is the alloy component Pr 40 Nd 10 Cu 40 Ga 10 (atomic ratio) of amorphous quenched strip.

[0092] S2: The main phase alloy ribbon obtained in step S1 is mixed with the related phase ribbon in a certain proportion, and mechanically crushed to allow the amorphous alloy and the main alloy to form a solid solution, thereby introducing the Cu-rich and Ga-rich phases in the grain boundaries; the mixed powder is crushed and pulverized, and the pulverizing process can be ball milling or air flow milling. A small amount of oxygen can be introduced during the pulverizing process to perform magnetic field forming to obtain a blank, and the magnetic field forming is to press-form on one side and magnetic field orientation on the other side at the same time; after magnetic field forming, isostatic pressing can be performed and then sintering and aging can be performed, or sintering and aging can be performed directly.

[0093] Specifically, in this embodiment, the weight ratio of the thin strip of the relevant phase is 4%, the mechanical crushing particle size is 15 μm, the air flow mill is used for crushing and powdering, the powder particle size D50 = 3.5 μm, and the blank density after magnetic field forming is 4.2 g / cm 3 .

[0094] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0095] Specifically, in this embodiment, the sintering temperature is 1100°C, and the temperature is kept for 4 hours; the first aging temperature is 850°C, and the temperature is kept for 3 hours; the second aging temperature is 450°C, and the temperature is kept for 3 hours. The final NdFeB rare earth magnet has the following components per unit mass percentage: PrNd content is 32%, Al content is 0.05%, B content is 0.85%, Co content is 2.0%, Cu content is 2.0%, Ga content is 0.4%, Zr content is 0.5%, and the rest is Fe and impurities. The C content in the impurities is 700ppm, the N content is 600ppm, and the O content is 800ppm. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data of the obtained NdFeB rare earth magnet measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument are shown in Table 1; the atomic percentage of each element in the NdFeB rare earth magnet is shown in Table 3.

[0096] Embodiment 3:

[0097] The present embodiment is different from the above-mentioned embodiment 1 in that the above-mentioned method for producing a NdFeB rare earth magnet comprises the following steps:

[0098] S1: subjecting the raw materials to hydrogen absorption and dehydrogenation treatments to obtain a hydrogen-treated main phase alloy ribbon and a related phase ribbon, respectively. The related phase ribbon may be a copper-rich gallium-rich phase ribbon, etc. The related phase ribbon is a rapidly quenched amorphous ribbon.

[0099] Specifically, the raw materials for preparing the thin strips of the main phase alloy and the thin strips of the related phases of the NdFeB rare earth magnet are determined by composition design. The raw materials used can be metal elements, alloys containing rare earth elements or alloys without rare earth elements, iron, ferroboron, etc. The hydrogen absorption and dehydrogenation treatment can be low-temperature hydrogen absorption treatment or high-temperature hydrogen absorption treatment, and the dehydrogenation treatment can be high-temperature dehydrogenation or low-temperature long-term dehydrogenation.

[0100] Specifically, in this embodiment, a low-temperature hydrogen absorption treatment is adopted, the hydrogen absorption temperature is 100°C, the dehydrogenation temperature is 550°C, the dehydrogenation time is 4 hours, and the thin strip of the relevant phase is the alloy component Pr 50 Nd 10 Cu 20 Ga 20 (atomic ratio) of amorphous quenched strip.

[0101] S2: The main phase alloy ribbon obtained in step S1 is mixed with the related phase ribbon in a certain proportion, and mechanically crushed to allow the amorphous alloy and the main alloy to form a solid solution, thereby introducing the Cu-rich and Ga-rich phases in the grain boundaries; the mixed powder is crushed and pulverized, and the pulverizing process can be ball milling or air flow milling. A small amount of oxygen can be introduced during the pulverizing process to perform magnetic field forming to obtain a blank, and the magnetic field forming is to press-form on one side and magnetic field orientation on the other side at the same time; after magnetic field forming, isostatic pressing can be performed and then sintering and aging can be performed, or sintering and aging can be performed directly.

[0102] Specifically, in this embodiment, the weight ratio of the thin ribbon of the relevant phase is 3%, the mechanical crushing particle size is 10 μm, the air flow mill is used for crushing and powdering, the powder particle size D50 = 3.8 μm, and the density of the blank after magnetic field forming is 4.0 g / cm 3 .

[0103] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0104] Specifically, in this embodiment, the sintering temperature is 1050°C, and the temperature is kept for 6 hours; the first-stage aging temperature is 750°C, and the temperature is kept for 5 hours; the second-stage aging temperature is 480°C, and the temperature is kept for 4 hours. The final NdFeB rare earth magnet has the following components per unit mass percentage: PrNd content is 30.8%, Al content is 0.07%, B content is 0.90%, Co content is 0.50%, Cu content is 0.70%, Ga content is 0.60%, Zr content is 0.3%, and the rest is Fe and impurities. The C content in the impurities is 650ppm, the N content is 700ppm, and the O content is 700ppm. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data of the obtained NdFeB rare earth magnet measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument are shown in Table 1; the atomic percentage of each element in the NdFeB rare earth magnet is shown in Table 3.

[0105] Embodiment 4:

[0106] The present embodiment is different from the above-mentioned embodiment 1 in that the above-mentioned method for producing a NdFeB rare earth magnet comprises the following steps:

[0107] S1: subjecting the raw materials to hydrogen absorption and dehydrogenation treatments to obtain a hydrogen-treated main phase alloy ribbon and a related phase ribbon, respectively. The related phase ribbon may be a copper-rich gallium-rich phase ribbon, etc. The related phase ribbon is a rapidly quenched amorphous ribbon.

[0108] Specifically, the raw materials for preparing the thin strips of the main phase alloy and the thin strips of the related phases of the NdFeB rare earth magnet are determined by composition design. The raw materials used can be metal elements, alloys containing rare earth elements or alloys without rare earth elements, iron, ferroboron, etc. The hydrogen absorption and dehydrogenation treatment can be low-temperature hydrogen absorption treatment or high-temperature hydrogen absorption treatment, and the dehydrogenation treatment can be high-temperature dehydrogenation or low-temperature long-term dehydrogenation.

[0109] Specifically, in this embodiment, a normal temperature hydrogen absorption treatment is adopted, the dehydrogenation temperature is 650°C, the dehydrogenation time is 3 hours, and the thin strip of the relevant phase is the alloy component Pr 40 Nd 10 Cu 40 Ga 10 (atomic ratio) of amorphous quenched strip.

[0110] S2: The main phase alloy ribbon obtained in step S1 is mixed with the related phase ribbon in a certain proportion, and mechanically crushed to allow the amorphous alloy and the main alloy to form a solid solution, thereby introducing the Cu-rich and Ga-rich phases in the grain boundaries; the mixed powder is crushed and pulverized, and the pulverizing process can be ball milling or air flow milling. A small amount of oxygen can be introduced during the pulverizing process to perform magnetic field forming to obtain a blank, and the magnetic field forming is to press-form on one side and magnetic field orientation on the other side at the same time; after magnetic field forming, isostatic pressing can be performed and then sintering and aging can be performed, or sintering and aging can be performed directly.

[0111] Specifically, in this embodiment, the weight ratio of the thin strip of the relevant phase is 3.5%, the mechanical crushing particle size is 25 μm, the air flow mill is used for crushing and powdering, the powder particle size D50 = 4.0 μm, and the density of the blank after magnetic field forming is 4.4 g / cm 3 .

[0112] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0113] Specifically, in this embodiment, the sintering temperature is 1060°C, and the temperature is kept for 8 hours; the first-stage aging temperature is 700°C, and the temperature is kept for 7h; the second-stage aging temperature is 500°C, and the temperature is kept for 3h. The final NdFeB rare earth magnet has the following components per unit mass percentage: PrNd content is 31.5%, Al content is 0.35%, B content is 0.94%, Co content is 0.8%, Cu content is 1.2%, Ga content is 0.3%, Ti content is 0.15%, and the rest is Fe and impurities. The C content in the impurities is 750ppm, the N content is 500ppm, and the O content is 700ppm. The NdFeB rare earth magnet obtained is measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data are shown in Table 1, and the atomic percentage of each element in the NdFeB rare earth magnet is shown in Table 3.

[0114] Embodiment 5:

[0115] The present embodiment is different from the above-mentioned embodiment 1 in that the above-mentioned method for producing a NdFeB rare earth magnet comprises the following steps:

[0116] S1: subjecting the raw materials to hydrogen absorption and dehydrogenation treatments to obtain a hydrogen-treated main phase alloy ribbon and a related phase ribbon, respectively. The related phase ribbon may be a copper-rich gallium-rich phase ribbon, etc. The related phase ribbon is a rapidly quenched amorphous ribbon.

[0117] Specifically, the raw materials for preparing the thin strips of the main phase alloy and the thin strips of the related phases of the NdFeB rare earth magnet are determined by composition design. The raw materials used can be metal elements, alloys containing rare earth elements or alloys without rare earth elements, iron, ferroboron, etc. The hydrogen absorption and dehydrogenation treatment can be low-temperature hydrogen absorption treatment or high-temperature hydrogen absorption treatment, and the dehydrogenation treatment can be high-temperature dehydrogenation or low-temperature long-term dehydrogenation.

[0118] Specifically, in this embodiment, a room temperature hydrogen absorption treatment is adopted, the dehydrogenation temperature is 500°C, the dehydrogenation time is 7 hours, and the thin strip of the relevant phase is the alloy component Pr 50 Nd 10 Cu 40 (atomic ratio) of amorphous quenched strip.

[0119] S2: The main phase alloy ribbon obtained in step S1 is mixed with the related phase ribbon in a certain proportion, and mechanically crushed to allow the amorphous alloy and the main alloy to form a solid solution, thereby introducing the rich Cu in the grain boundary; the mixed powder is crushed to make powder, and the powder making process can be ball milling or air flow milling. A small amount of oxygen can be introduced during the powder making process to perform magnetic field forming to obtain a blank, and the magnetic field forming is to press-form on one side and magnetic field orientation on the other side at the same time; after magnetic field forming, isostatic pressing can be performed and then sintering and aging can be performed, or sintering and aging can be performed directly.

[0120] Specifically, in this embodiment, the weight ratio of the thin ribbon of the relevant phase is 2%, the mechanical crushing particle size is 10 μm, the air flow mill is used for crushing and powdering, the powder particle size D50 = 4.5 μm, and the density of the blank after magnetic field forming is 4.1 g / cm 3 .

[0121] S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

[0122] Specifically, in this embodiment, the sintering temperature is 950°C, and the temperature is kept for 15 hours; the first-stage aging temperature is 900°C, and the temperature is kept for 4 hours; the second-stage aging temperature is 550°C, and the temperature is kept for 3 hours. The final NdFeB rare earth magnet has the following components per unit mass percentage: PrNd content is 33.5%, Al content is 0.8%, B content is 1.05%, Co content is 1.5%, Cu content is 0.8%, Ga content is 0.20%, Ti content is 0.10%, and the rest is Fe and impurities. The C content in the impurities is 500ppm, the N content is 400ppm, and the O content is 400ppm. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data of the obtained NdFeB rare earth magnet measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument are shown in Table 1; the atomic percentage of each element in the NdFeB rare earth magnet is shown in Table 3.

[0123] The difference between Comparative Examples 1 to 5 and Examples 1 to 5 is only that the second aging temperature is different. The remanence (Br), coercive force (Hcj) and square (Hk / Hcj) data of the NdFeB rare earth magnets obtained in Comparative Examples 1 to 5 are measured at room temperature of 20°C using a NIM-2000 magnetic property measuring instrument, as shown in Table 2.

[0124] Table 1: Remanence (Br), coercivity (Hcj) and squareness (Hk / Hcj) data

[0125]

[0126] Table 2: Remanence (Br), coercivity (Hcj) and squareness (Hk / Hcj) data

[0127]

[0128] By comparing Table 1 with Table 2, it is found that the aging temperature has a great influence on the diffusion performance, as follows:

[0129] Example 1 process parameters: sintering temperature 1070 ° C, sintering time is 6h, the first aging temperature is 880 ° C, the first aging time is 3h, the second aging temperature is 430 ° C, the second aging time is 7h, the magnet performance is Br = 14.4kGs, Hcj = 19kOe, Hk / Hcj = 0.98, it can be seen from Comparative Example 1 that the difference between them is that the remanence (Br) and the square (Hk / Hcj) are basically unchanged, and the coercive force (Hcj) has an obvious difference, which is 2kOe, indicating that the aging temperature has a greater influence on the coercive force performance of the magnet.

[0130] Example 2 process parameters: sintering temperature 1100 ° C, sintering time is 4h, the first aging temperature is 850 ° C, the first aging time is 3h, the second aging temperature is 450 ° C, the second aging time is 3h, the magnet performance is Br = 13.5kGs, Hcj = 24.5kOe, Hk / Hcj = 0.98, it can be seen from Comparative Example 2 that their difference is that the remanence (Br) and square (Hk / Hcj) are basically unchanged, while the coercive force (Hcj) has an obvious difference of 2kOe, indicating that the aging temperature has a greater influence on the coercive force performance of the magnet.

[0131] Example 3 process parameters: sintering temperature 1050°C, sintering time is 5h, first aging temperature is 750°C, first aging time is 5h, second aging temperature is 480°C, second aging time is 4h, magnet performance is Br=14.0kGs, Hcj=22kOe, Hk / Hcj=0.98. It can be seen from Comparative Example 3 that their difference is that while the remanence (Br) and square (Hk / Hcj) remain basically unchanged, the coercive force (Hcj) has an obvious difference of 3kOe, indicating that the aging temperature has a greater influence on the coercive force performance of the magnet.

[0132] Example 4 process parameters: sintering temperature 1060°C, sintering time is 8h, first aging temperature is 700°C, first aging time is 7h, second aging temperature is 500°C, second aging time is 3h, magnet performance is Br=13.2kGs, Hcj=23.5kOe, Hk / Hcj=0.98. It can be seen from Comparative Example 4 that their difference is that while the remanence (Br) and square (Hk / Hcj) remain basically unchanged, the coercive force (Hcj) has an obvious difference of 3kOe, indicating that the aging temperature has a greater influence on the coercive force performance of the magnet.

[0133] Example 5 process parameters: sintering temperature 950°C, sintering time is 15h, first aging temperature is 900°C, first aging time is 4h, second aging temperature is 550°C, second aging time is 3h, magnet performance is Br=12.3kGs, Hcj=26kOe, Hk / Hcj=0.98. It can be seen from Comparative Example 5 that their difference is that while the remanence (Br) and square (Hk / Hcj) remain basically unchanged, the coercive force (Hcj) has an obvious difference of 4kOe, indicating that the aging temperature has a greater influence on the coercive force performance of the magnet.

[0134] Table 3: Atomic percentage of each element in NdFeB rare earth magnets

[0135]

[0136] From Table 3 above, it can be seen that the NdFeB rare earth magnets in Examples 1 to 5 are mainly composed of a main phase, a two-grain grain boundary phase and a triangular region grain boundary phase, wherein the main phase is basically the same except for a slight difference due to the different ratios of PrNd or pure Nd in R. Figure 2-7 As shown, the position and range of the two-grain grain boundary phase and the triangular region grain boundary phase are clearly defined. The main phase, the two-grain grain boundary phase and the triangular region grain boundary phase are described as follows:

[0137] The average Cu / R values ​​within 20 nm of the two-grain grain boundary phase close to the main phase of Examples 1 to 5 are 1.6, 2, 1.7, 1.8, and 1.6, respectively. The average Cu / R values ​​within 50 nm of the grain boundary center of the two-grain grain boundary phase are 1.1, 1.5, 1.2, 1.2, and 1.2, respectively. There are needle-shaped high melting point phases in the two-grain grain boundary phases of Examples 1 to 5, and the widths are 15, 50, 20, 15, and 10 nm, respectively.

[0138] The triangular grain boundary phases of the two-grain grain boundary phases of Examples 1 to 5 all contain R-rich phases, FCC-type Nd-rich phases, and 6:14 phases. The average values ​​of Cu / R in the RCu phase satisfy 1.05, 1.5, 1.1, 1.3, and 1.1. The average values ​​of Ga / R in the RGa phase satisfy 0.15, 0.2, 0.5, 0.15, and 0.15. The triangular grain boundary phases of Examples 1 to 5 all contain needle-shaped high-melting-point phases, and the widths are 15, 50, 20, 15, and 10 nm, respectively. In summary, the NdFeB rare earth magnet obtained by this method does not contain heavy rare earth, has good magnet uniformity and good squareness, and the coercive force and remanence of the NdFeB rare earth magnet can be regulated by the design of the grain boundary phase. The grain boundary phase contains a thicker non-magnetic phase, which plays a good magnetic isolation role and increases the coercive force of the magnet. The grain boundary phase contains a uniform needle-shaped ZrBx phase or TiBx phase, which has a good high temperature resistance effect.

[0139] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A neodymium iron boron rare earth magnet, characterized in that: The NdFeB rare earth magnet is a sintered NdFeB permanent magnet, comprising a main phase, a two-grain grain boundary phase and a triangular region grain boundary phase; The main phase contains R2T 14 B phase, the unit is atomic percentage, R refers to at least one of Nd and Pr, T refers to at least Fe among Fe and Co; The two-grain grain boundary phase comprises: The content of the copper-rich phase at the grain boundary satisfies 1.5<Cu / R≤2 within 20nm near the main phase interface, and 1<Cu / R≤1.5 within 50nm at the center of the grain boundary. and / or needle-shaped ZrBx phase, with a width of 10 to 50 nm, and / or needle-shaped TiBx phase, with a width of 10 to 50 nm; The triangular region grain boundary phase includes: FCC-type NdOx phase, RCu phase, where 1<Cu / R≤1.5, RGa phase, where 0.1<Ga / R≤0.5, R-rich phase, 6:14 phase, and / or needle-shaped ZrBx phase with a width of 10 to 50 nm, and / or needle-shaped TiBx phase with a width of 10 to 50 nm.

2. The NdFeB rare earth magnet according to claim 1, characterized in that: The composition includes the following components based on the unit mass percentage of 100%: R: 29.5-33.5%; B: 0.85-1.05%; Al: 0.05-0.8%; Cu: 0.4-2.0%; Ga: 0.3-0.6%; Co: 0.5-2.0%; Zr or Ti: 0.15-0.5%, and the rest is Fe and inevitable impurities.

3. The NdFeB rare earth magnet according to claim 1, characterized in that: The R may further contain at least one of La, Ce, Sm, Y, Gd, Dy, Tb, and Ho.

4. A method for preparing the NdFeB rare earth magnet according to claim 1, characterized in that: The following steps are involved: S1: subjecting the raw material to hydrogen absorption and dehydrogenation treatment to obtain a thin strip of the main phase alloy and a thin strip of the related phase after hydrogen treatment, respectively; S2: Mix the main phase alloy ribbon obtained in step S1 with the related phase ribbon in a certain proportion, and mechanically crush them to allow the amorphous alloy and the main alloy to form a solid solution, crush the mixed powder into powder, and perform magnetic field molding to obtain a blank; S3: placing the blank into a sintering furnace, sintering and forming the blank and keeping the blank warm to obtain a sintered blank, and performing secondary aging treatment to obtain a NdFeB rare earth magnet.

5. A method for preparing the NdFeB rare earth magnet according to claim 4, characterized in that: In the step S1, the hydrogen absorption temperature is 50-100° C., the dehydrogenation temperature is 500-650° C., and the dehydrogenation time is 3-7 hours.

6. A method for preparing the NdFeB rare earth magnet according to claim 4, characterized in that: The mechanical crushing particle size in step S2 is 10-25 μm, and the powder particle size D50 obtained by crushing and pulverizing is 2-7 μm. The density of the blank is 4.0-4.5 g / cm 3 .

7. A method for preparing the NdFeB rare earth magnet according to claim 4, characterized in that: In the step S3, the sintering temperature is 950-1100° C. and the temperature is kept for 4-15 hours; the first-stage aging temperature is 700-900° C. and the temperature is kept for 3-7 hours; the second-stage aging temperature is 430-550° C. and the temperature is kept for 3-7 hours.

Citation Information

Patent Citations

  • RTB series sintered magnets

    CN110299237B

  • RTB series permanent magnets

    CN111724959B

Cited By

  • Neodymium-iron-boron magnet and preparation method thereof

    CN120636993A

  • Neodymium-iron-boron magnet based on grain boundary carbon hierarchical regulation and preparation method thereof

    CN121171732A

  • Neodymium-iron-boron magnet based on hierarchical regulation of grain boundary carbon and preparation method thereof

    CN121171732B